EXPLORING PR AGENCY PERSPECTIVES ON INFLUENCER MARKETING IN DELHI NCR - Chanda, Kiran; Jain, Riyanka (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the role of influencer marketing in the fashion retail sector of Delhi NCR, focusing on qualitative insights from PR agencies that actively manage influencer campaigns. With the growing dominance of digital marketing, influencer collaborations have become a key strategy for brands seeking to enhance consumer engagement and brand positioning. Using QDA Lite for data analysis, the research identifies critical themes shaping influencer marketing strategies, including authenticity, appeal, trustworthiness, competence, and inventiveness. Through in-depth interviews with PR professionals, this study examines how these attributes influence consumer perception and purchasing behavior. The research adopts a systematic coding approach to extract meaningful insights from interview data, allowing for a comprehensive understanding of the factors that drive successful influencer-brand partnerships. Findings suggest that authenticity and trustworthiness serve as fundamental pillars of effective influencer collaborations, ensuring credibility and long-term consumer loyalty. Additionally, appeal and inventiveness play a crucial role in capturing audience attention and fostering deeper engagement, while competence enhances an influencer's ability to communicate brand messages effectively. The study also highlights the challenges faced by PR agencies, including measuring campaign effectiveness, selecting the right influencers, and managing audience skepticism. It offers practical recommendations for brands and PR agencies to refine their influencer marketing strategies by leveraging industry expertise and addressing real-world obstacles. By bridging the gap between academic research and industry practice, this study provides valuable insights for marketing professionals looking to optimize influencer collaborations in the dynamic and competitive landscape of Delhi NCR's fashion retail sector.